Effect of geomembrane hole geometry on leakage overlain by saturated tailings. Issue 6 (December 2021) - Rowe, R. Kerry; Fan, Jiying
Abstract: Experiments are conducted to quantify leakage through holes in a geomembrane (GMB) overlain by tailings with 30% fines and underlain by a well-graded gravel. Analytical and empirical equations for predicting leakage through a circular hole are used to analyze the data. Test results show that changing the hole shape from circular to noncircular increases the leakage. Leakage through 2000 mm 2 triangular, diamond, and square holes are all 15% higher than the 2000 mm 2 circular hole. An increase by up to 33% is observed for a rectangular hole. The analytical equations for predicting leakage and head loss through a hole given by the modified Rowe-Booker equation are experimentally verified. The spatial distribution of fines content within about five diameters of the hole is shown to have a notable impact on leakage. Up to a 100% increase in leakage is detected due to 3% reduction in the fines content around the hole. For homogeneous tailings, the ratio of head loss within the hole and above the hole to total head loss are independent of consolidation stress and water head and primarily depend on the hole geometry (i.e., shape and size). Finally, the combined effect of tailings thickness and water head on leakage is discussed. Highlights: First experimental research on the effect of noncircular hole shape on leakage through geomembrane in tailings storage application. First experimental research on the impact of tailings heterogeneity on leakage. Verify the analytical and empirical equations to predict leakage through a circular geomembrane hole overlain by saturated tailings. Explore the hole shape factors for the noncircular hole in terms of leakage prediction.